Hub network design problems with profits - Alibeyg, Armaghan; Contreras, Ivan; Fernández, Elena (Transportation research. Part E, Logistics and transportation review, 2016)
•New class of hub network design problems with profit-oriented objectives.•Potential applications in the design of air and ground transportation networks.•Simultaneous optimization of collected profit, setup cost of hub network and transportation cost.•Alternative models and integer programming formulations proposed and analyzed.•Results from computational tests highlight the superiority for these models for decision-making. This paper presents a class of hub network design problems with profit-oriented objectives, which extend several families of classical hub location problems. Potential applications arise in the design of air and ground transportation networks. These problems include decisions on the origin/destination nodes that will be served as well as the activation of different types of edges, and consider the simultaneous optimization of the collected profit, setup cost of the hub network and transportation cost. Alternative models and integer programming formulations are proposed and analyzed. Results from computational experiments show the complexity of such models and highlight their superiority for decision-making.